Full Vowel/Schwa Alternations in the Perfective of Moroccan Arabic Hollow Verbs - El-farhaoui, M'barek; Daouia , Laaboudi; Mohamed , Marouane (International Journal of Linguistics and Translation Studies, 2024)
This paper purports to investigate full vowel/schwa (V/ə) alternations in the perfective of Moroccan Arabic (MA) hollow verbs. Earlier treatments on this issue show that the perfective schwa is derived from full vowels by a special reduction rule applying before /CC/ cluster within the core stem. These accounts fail to give convincing analyses since they make recourse to unmotivated rules and neglect to consider the bimoraicity prosodic requirement in the perfective of MA hollow verbs. The main aim of the present paper is to address this gap in the literature by conducting an Optimality Theory (OT) analysis of V/ə alternations as a result of Foot-Binarity (FT-BIN) in terms of bimoraicity. To achieve this objective, we rely on secondary data, which is taken from published grammar works. The major finding of the paper is that full vowels alternate with schwa in the perfective of MA CVC verbs to achieve the bimoraicity prosodic requirement. This finding provides a strong proponent in favour of the use of the mora in the analysis of V/ə alternations and enhances our understanding of the phonology of MA verbs.